1994
DOI: 10.1902/jop.1994.65.4.291
|View full text |Cite
|
Sign up to set email alerts
|

Dentin Hypersensitivity. Occlusion of Dentinal Tubules by Brushing With and Without an Abrasive Dentifrice

Abstract: Daily toothbrushing with and without an abrasive dentifrice was performed on the ground surfaces of human cervical dentin attached to resin plates, which had been exposed to the oral cavities of 4 subjects for 8 weeks. Brushing with a dentifrice containing calcium hydrogen phosphate as an abrasive caused most of the dentinal tubules to open. The patency of dentinal tubules is thought to induce dentin hypersensitivity. Brushing without a dentifrice, on the other hand, resulted in occlusion of the dentinal tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
0
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
4
33
0
6
Order By: Relevance
“…These results were also found in other studies (6,13). The acid beverages that caused the highest increase in dentin permeability were lemon juice (187.83%), orange juice (148.33%), vinegar (147.16%), cola drink (139.83%) and white wine (184%).…”
Section: Orange Juicesupporting
confidence: 86%
See 2 more Smart Citations
“…These results were also found in other studies (6,13). The acid beverages that caused the highest increase in dentin permeability were lemon juice (187.83%), orange juice (148.33%), vinegar (147.16%), cola drink (139.83%) and white wine (184%).…”
Section: Orange Juicesupporting
confidence: 86%
“…Thus, the changes in permeability in this experiment were considered a percentage of Stage 1, using the Lp value as 100% flow permits evaluation of modifications in dentin permeability following the test treatments. Each specimen was its own control (4,6,11,12). This study showed that exposure to acidic beverages removed the smear layer surface and increased dentin permeability.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In contrast, dentinal tubules were gradually obturated by precipitation of calcium and phosphate when plaque control was exercised through daily brushing or chemical removal of plaque using chlorhexidine9, 16) Therefore, the condition of plaque control markedly affected the pathology of hypersensitive dentin12) . In addition, acidic beverages remove the smear layer and open dentinal tubules17) .…”
Section: Statistical Analysis For Statisticalmentioning
confidence: 99%
“…Os dentes mais acometidos são os pré-molares e os sintomas estão intimamente relacionados com a recessão gengival (CHRYSANTHAKOPOULOS, 2011;YE;FENG;LI, 2012), ou seja, exposição da dentina radicular e/ou cemento. Uma vez expostos ao meio bucal, esses tecidos estão mais suscetíveis à erosão intrínseca ou extrínseca (alimentos e bebidas ácidas) e também à abrasão causada pela escovação, processos esses capazes de expor e abrir os túbulos dentinários (KUROIWA, 1994;WATSON;THOMPSON, 2010). A literatura demonstra que existe uma relação direta entre túbulos dentinários abertos, permeabilidade e hipersensibilidade dentinária, ou seja, quanto maior a permeabilidade, maior a hipersensibilidade clínica (PINTO et al, 2010).…”
Section: Discussionunclassified